Cleaner production assessment and improvement strategies in a textile industry / Shaqina Ramlan - Shaqina, Ramlan (2019)
This study was conducted in a textile manufacturing factory in order to evaluate the environmental and economic feasibility of Cleaner Production (CP) strategies. The aim of this study is to reduce the carbon footprint in the textile manufacturing processes. The quantification of the total resource consumption, energy consumption and waste generation and disposal was obtained through CP audit. The audit showed that the main contributors of CO2 emission of the factory were electricity, water, fuel, chemical and raw material consumption as well as solid waste, scheduled waste and wastewater generation. The result from the audit showed that the CO2 emission in this factory was 3,700 kgCO2 per ton of fabric whereby it constitutes mainly of fuel and electricity with 57% and 41% respectively. From 24 CP options identified, 11 CP options were recommended based on their feasibility. Therefore, the CO2 emission is expected to be reduced to 3,400 kgCO2 per ton of fabric which is equivalent to 8% in reduction of CO2 emission. The estimated investment cost required for the carbon footprint reduction was RM43,815 with a return on investment of 1.1 years. Thus, this shows that the CP strategies recommended is possible of reducing CO2 emission in a textile manufacturing factory.